Analysis of Seroreactivity against Cell Culture–Derived Bartonella spp. Antigens in Dogs. (16th December 2013) - Hegarty, B.C.; Bradley, J.M.; Lappin, M.R.; Balakrishnan, N.; Mascarelli, P.E.; Breitschwerdt, E.B.
<x xml:space="preserve">Abstract</x> Background Little is known about the specificity of Bartonella spp. immunofluorescent antibody (IFA) assays in dogs. Bacteremia in sick dogs most often has been associated with Bartonella henselae (Bh), Bartonella vinsonii subspecies berkhoffii (Bvb), and Bartonella koehlerae (Bk). Clarification of the diagnostic utility of IFA serology when testing against these organisms is needed. Objective To evaluate the specificity of Bartonella IFA assays utilizing 6 cell culture–grown antigen preparations. Animals Archived sera from SPF dogs (n = 29) and from dogs experimentally infected with Bvb (n = 10) and Bh (n = 3). Methods Antibodies (Abs) to Bvb genotypes I, II, and III, Bh serotype I, strains H‐1 and SA2, and to Bk were determined by IFA testing. Results Serum from naïve SPF dogs shown to be negative for Bartonella bacteremia did not react with any of the 6 Bartonella antigens by IFA testing. Dogs experimentally infected with Bvb genotype I developed Abs against homologous antigens, with no cross‐reactivity to heterologous Bvb genotypes, Bh H‐1, SA2 strains, or to Bk. Dogs experimentally infected with Bh serotype I developed Abs against Bh H‐1, but not to Bh SA2 strain with no cross‐reactive Abs to Bvb genotypes I–III or to Bk. Conclusions and Clinical Importance Bartonella spp. Ab responses during acute experimental infections are species and type specific.